Ethic of responsibility and the future of nature - Kulic, Miso (Journal of Economic Development, Environment and People, 2012)
The question of science is the one that concerns the very foundations of our reality and, in addition to that, it is a question that deals not only with our natural reality, with what was once called the "natural nature", but also with social and technological reality produced by science itself, which for a long time now is our second nature. Science has become not only the instrument by which we try to understand the reality of nature, through the process of creating reality, forming and transforming nature, it has become the reality in which we live itself, and without which, as it seems, we could hardly go on living. However, even though science as an instrument for understanding reality has become the reality which we have produced ourselves, we are still, paradoxically enough, far from answering the essential question: What is science? Since the question of science is at the same time the one of the production of reality, it is obvious that the question "what is science?" does not amount to a self-evident question asked by a scientist regarding his scientific field. It is not only a question concerning the nature of scientific knowledge, or of scientific methods of scientific results achieved. What is at stake here is the insight concerning social and political usage of science, that the reality, which is produced by the sciences, reveals to us even in the forms of its deification, manipulation, ideologization and virtualization. Is persevering in its science-Enlightenment paradigm of human emancipation or does it, on the wave of critical self-reflection spanning all the way through the 20th century, more and more question, as Paul Feyerabend (Against Method) does, the extent of constraints imposed on free thought which it produces itself? Of course, the other side of the questioning itself belongs here too: scientific progress can be evaluated regardless of its consequences, of the dangerous threats it poses to our future: nuclear annihilation, ecological pollution or climate changes which endanger the survival of the living world ?